Increased AGE-RAGE ratio in idiopathic pulmonary fibrosis. Issue 1 (December 2016) - Machahua, Carlos; Montes-Worboys, Ana; Llatjos, Roger; Escobar, Ignacio; Dorca, Jordi; Molina-Molina, Maria; Vicens-Zygmunt, Vanesa
Abstract Background The abnormal epithelial-mesenchymal restorative capacity in idiopathic pulmonary fibrosis (IPF) has been recently associated with an accelerated aging process as a key point for the altered wound healing. The advanced glycation end-products (AGEs) are the consequence of non-enzymatic reactions between lipid and protein with several oxidants in the aging process. The receptor for AGEs (RAGEs) has been implicated in the lung fibrotic process and the alveolar homeostasis. However, this AGE-RAGE aging pathway has been under-explored in IPF. Methods Lung samples from 16 IPF and 9 control patients were obtained through surgical lung biopsy. Differences in AGEs and RAGE expression between both groups were evaluated by RT-PCR, Western blot and immunohistochemistry. The effect of AGEs on cell viability of primary lung fibrotic fibroblasts and alveolar epithelial cells was assessed. Cell transformation of fibrotic fibroblasts cultured into glycated matrices was evaluated in different experimental conditions. Results Our study demonstrates an increase of AGEs together with a decrease of RAGEs in IPF lungs, compared with control samples. Two specific AGEs involved in aging, pentosidine and Nε-Carboxymethyl lysine, were significantly increased in IPF samples. The immunohistochemistry identified higher staining of AGEs related to extracellular matrix (ECM) proteins and the apical surface of the alveolar epithelial cells (AECs) surrounding fibroblast foci in fibrotic lungs. On the other hand, RAGE location was present at the cell membrane of AECs in control lungs, while it was almost missing in pulmonary fibrotic tissue. In addition, in vitro cultures showed that the effect of AGEs on cell viability was different for AECs and fibrotic fibroblasts. AGEs decreased cell viability in AECs, even at low concentration, while fibroblast viability was less affected. Furthermore, fibroblast to myofibroblast transformation could be enhanced by ECM glycation. Conclusions All of these findings suggest a possible role of the increased ratio AGEs-RAGEs in IPF, which could be a relevant accelerating aging tissue reaction in the abnormal wound healing of the lung fibrotic process.